Next Steps for Mind, Brain, and Education: Strengthening Early‐Career Development. Issue 3 (27th May 2019) - Gotlieb, Rebecca J. M.; Pollack, Courtney; Younger, Jessica W.; Toomarian, Elizabeth Y.; Allaire‐Duquette, Geneviève; Mariager, Nadja M.
ABSTRACT: An increasing number of scholars are being trained in the field of mind, brain, and education (MBE), yet discussions of trainees' needs and how to meet them are rare. We, the inaugural International Mind, Brain, and Education Society (IMBES) Trainee Board, identify three broad needs of MBE trainees: guidance and support, greater access to and connections among the MBE community, and professional development. We report a first step to address these needs: a daylong trainee conference, which included sessions to foster connections among trainees, provide mentorship from MBE leaders, and provide knowledge and skill building for careers. Attendees' survey results suggest the conference successfully supported trainees' development. As substantial trainee needs remain, we offer specific ways that principal investigators, institutions, funding agencies, future IMBES trainee boards, and the MBE community can further address trainees' needs to support early‐career development and strengthen the MBE field generally.